2015
DOI: 10.3109/15368378.2015.1076447
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency electromagnetic radiation exposure inside the metro tube infrastructure in Warszawa

Abstract: Antennas from various wireless communications systems [e.g. mobile phones base transceiver stations (BTS) and handsets used by passengers, public Internet access, staff radiophone transmitters used between engine-drivers and traffic operators] emitting radiofrequency electromagnetic radiation (RF-EMR) are used inside underground metro public transportation. Frequency-selective exposimetric investigations of RF-EMR exposure inside the metro infrastructure in Warsaw (inside metro cars passing between stations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A study by Gryz et al [63] investigated the levels of RF-EMF exposure inside the metro infrastructure in Warsaw by frequency-selective exposimeters. Results showed that most of the exposure was due to mobile phones base transceiver stations and handsets used by the passengers (GSM 900 and UMTS 2100) and to local wireless Internet access (WiFi 2G).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Gryz et al [63] investigated the levels of RF-EMF exposure inside the metro infrastructure in Warsaw by frequency-selective exposimeters. Results showed that most of the exposure was due to mobile phones base transceiver stations and handsets used by the passengers (GSM 900 and UMTS 2100) and to local wireless Internet access (WiFi 2G).…”
Section: Resultsmentioning
confidence: 99%
“…Grytz and Karpowicz ( 33 ) measured RF radiation inside the metro in Warsaw. The major source of exposure was the 900 GSM system.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in this area on public exposure, other than for example outdoor exposure in urban and rural areas in Sweden ( 31 ), in a workplace ( 32 ), the metro in Warsaw ( 33 ) and a study with body-worn exposimeters in The Netherlands ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is explained by the fact that trams run mainly in or close to the central business district of the cities. Furthermore, [9] analyzes the RF-EMF exposure levels within a metro by means of frequency-selective exposimeters, concluding that the most significant levels of exposure were caused by mobile phones used by the passengers and local wireless Internet connections (Wi-Fi 2G). Other authors in [10], [11] assessed the impact in RF-EMF exposure within a train having a femtocell within the wagon infrastructure.…”
Section: Introductionmentioning
confidence: 99%